Analysis of the reasons for the decline in the level of physical fitness of students - Groshevihin, I.V.; Grigan, S.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to analyse the reasons for the decline in students’ performance. During the analysis, a sociological survey was conducted, with respondents being first- to fourth-year students (bachelors) at higher education institutions. Methods and structure of the study. In solving the first task, methods of analysis and literature review were used, which showed that the primary and main problems of low physical activity are lack of time among students, a sedentary lifestyle, lack of motivation, and stress. To solve the second task, a sociological survey was conducted, with respondents being students of higher educational institutions in their first to fourth years (bachelors). Results and conclusions. Lack of free time is the main problem in reducing the level of physical fitness among students. As soon as an applicant becomes a student, they are assigned a large number of new responsibilities that are not comparable to those at school. In this situation, it is difficult to properly organise the learning process and allocate time for physical education and sports. In conclusion, it is important to note that students and young people are at increased risk in terms of health and physical development. In this regard, it is necessary to take action to address these issues, including through the organisation of appropriate educational programmes and activities.